Has the North Pole been discovered? [electronic resource] : an analytical and synthetical review of the published narratives of the two Arctic explorers, Dr. Frederick A. Cook, and civil engineer, Robert E. Peary, U. S.N. : also a review of the action of the U.S. government - Hall, Thomas F., 1841-1933. (Boston : R.C. Badger, 1917)
Tables. Includes appendixes and an index. Electronic reproduction. Mode of access: Internet. 44